The relationship between trades of foreign institutional and retail investors and equity return - Ros Zam Zam Sapian (Penerbit Universiti Kebangsaan Malaysia, 2015)
This study examined the relationship between equity flows and domestic equity returns using daily aggregate trade data categorized by two foreign investors’ classes; namely foreign institutional and retail investors. To explore the relationship between domestic equity returns and both buy and sale trades of foreign institutional and retail investors, this study employed bivariate vector autoregressive model and impulse response functions. The main finding of this study amongst others indicated that past equity returns do impact the sale trades of both foreign institutional and retail investors; however they are inversely related. The findings indicated that foreign institutional investors sell less during market upswing, while foreign retail investors sell more during upside market momentum. The finding of this study also revealed that there is a temporary impact of foreign retail investors’ buy trades on domestic equity returns, thus supports the information dissemination concept particularly with regard to price momentum.